Sonophotocatalytic degradation of reactive black 5 in simulated dye wastewater using ZnO and activated red mud sonophotocatalyst - Vigneswar Krishnan; Collin G. Joseph; Yun Hin Taufq‑Yap; Siow Hwa Teo; Sabrina Soloi; Newati Wid; Mohd Hafz Abd Majid; Yan Yan Farm; Kenneth F. Rodrigues (Springer, 2024)
In this study, an anionic dye, Reactive Black 5 (RB5), was subjected to sonophotocatalytic treatment process with the aim of establishing the efectiveness of the prepared ZnO incorporated activated red mud (ZnO/ARM) as a viable sonophotocatalyst. ZnO/ARM was prepared by impregnation method at diferent weight ratios (0.25:1, 0.5:1, 0.75:1 and 1:1) with the ZnO/ ARM at weight ratio of 0.75:1 proving to be the best sonophotocatalyst. The prepared sonophotocatalysts were characterized by X-ray difractometer for crystal phase studies, Brunauer–Emmett–Teller for surface area studies, Fourier transform infrared for surface functional groups studies, SEM–EDX for surface morphological and elemental studies, difuse refectance spectroscopy and photoluminescence for sonophotocatalyst band-gap studies while parametric and kinetic studies of the removal of RB5 from the simulated wastewater were conducted to confrm its efectiveness under simultaneous application of a transducer bath-type sonicator (35 kHz) and a UV-C (254 nm) lamp. The infuence of the solution pH, concentration and catalyst dosage were manipulated throughout this study to investigate the sonophotodegradation kinetics and synergistic efects on the RB5 degradation. Experimental results confrmed that the sonophotocatalytic degradation rate of 20 ppm RB5 was most efective under acidic medium (66.7%) as compared to alkaline medium (46.1%) due to an excess of positive charge in the ZnO/ARM surface which favours a strong electrostatic interaction with SO3 − groups of the dye resulting in a higher degradation rate (0.0156 min−1). Under alkaline conditions, the catalytic activity of ZnO/ARM was attenuated by the higher negative charge which promoted the repulsion of the dye from ZnO/ARM surfaces leading to a lower degradation rate of 0.01 min−1. The accelerated photo induced electron–hole transfer and separation, decreased recombination rate and band energy matching, enhancing the photocatalytic performance of ZnO/ARM composite.